Efektivitas Penerapan Aplikasi Sistem Keuangan Desa (Siskeudes) Dalam Tata Kelola Keuangan Desa Naunu Kecamatan Fatuleu Kabupaten Kupang Nusa Tenggara Timur - Zeferio Da Costa Nunes; Petrus Emanuel De Rozari; Eve Ida Malau (STIE AMKOP, 2025)
This study aims to analyze the effectiveness of implementing the Village Financial System (Siskeudes) application in the financial management of Naunu Village, Fatuleu District, Kupang Regency, focusing on achievement results, the availability of human resources (HR) and infrastructure, as well as the stages of the financial management process. The research employed a descriptive qualitative method through interviews, observations, and documentation studies. The findings reveal that since its implementation in 2019, Siskeudes has improved transparency, accountability, and orderliness in village financial management, as reflected in the increase of Naunu Village’s Village Development Index (IDM) status to a developing village in 2023. However, full effectiveness has not yet been achieved due to limited HR capacity, with most village officials only graduating from senior high school, the workload being concentrated on a single operator who also serves as the village treasurer, and inadequate infrastructure such as limited computer units and unstable internet connectivity. The study concludes that while the implementation of Siskeudes in Naunu Village has generally been successful, further optimization is needed through capacity building for village officials, workload distribution, and the provision of better supporting infrastructure. Keywords: Siskeudes, Village Financial Management, Effectiveness